2005
DOI: 10.1128/jvi.79.22.13892-13899.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Polyprotein Processing and RNA Replication of Human Rhinovirus by Pyrrolidine Dithiocarbamate Involves Metal Ions

Abstract: Pyrrolidine dithiocarbamate (PDTC) is an antiviral compound that was shown to inhibit the replication of human rhinoviruses (HRVs), poliovirus, and influenza virus. To elucidate the mechanism of PDTC, the effects on the individual steps of the infection cycle of HRV were investigated. PDTC did not interfere with receptor binding or internalization by receptor mediated endocytosis of HRV2 particles into HeLa cells. But we demonstrate that the processing of the viral polyprotein was prevented by PDTC treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 48 publications
2
46
0
Order By: Relevance
“…In addition to the use of disulfiram in alcohol aversion therapy (Eneanya et al, 1981), and N,Ndiethyldithiocarbamate in the treatment of nickel carbonyl intoxication (Sunderman, 1979), a wide range of new medical applications for dithiocarbamates are currently being explored. Investigations have presented support for potential uses of dithiocarbamates in treating cocaine addiction (Sofuoglu and Kosten, 2005), inflammation (Fang et al, 2005), viral infections (Krenn et al, 2005;Si et al, 2005), and as adjuncts for chemotherapy (Bach et al, 2000). In vitro mechanistic studies have demonstrated the ability of dithiocarbamates to modulate numerous biological processes including apoptosis, oxidative stress, and transcription, providing the molecular basis for these proposed medical applications (Kang et al, 2001;Kimoto-Kinoshita et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the use of disulfiram in alcohol aversion therapy (Eneanya et al, 1981), and N,Ndiethyldithiocarbamate in the treatment of nickel carbonyl intoxication (Sunderman, 1979), a wide range of new medical applications for dithiocarbamates are currently being explored. Investigations have presented support for potential uses of dithiocarbamates in treating cocaine addiction (Sofuoglu and Kosten, 2005), inflammation (Fang et al, 2005), viral infections (Krenn et al, 2005;Si et al, 2005), and as adjuncts for chemotherapy (Bach et al, 2000). In vitro mechanistic studies have demonstrated the ability of dithiocarbamates to modulate numerous biological processes including apoptosis, oxidative stress, and transcription, providing the molecular basis for these proposed medical applications (Kang et al, 2001;Kimoto-Kinoshita et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that copper and zinc ions inhibit influenza virus RNA-dependent RNA polymerase activity, and that the inhibitory effect of bathocuproine-copper and bathocuproine-zinc complexes is greater than that of bathocuproine itself [40]. Moreover, it has been known that PDTC-copper and PDTC-zinc complexes (9 and 10, respectively, Figure 3) inhibited the replication of Coxsackie virus [41] and rhinovirus [42]. Conceivably, PDTC may inhibit influenza virus gene replication and transcription through the inhibition of viral RNA-dependent RNA polymerase activity by increasing the amount of intracellular copper and zinc ions or intracellular PDTC-copper and PDTC-zinc complexes, but further study is needed to elucidate the precise mechanism of inhibitory effect of PDTC on influenza virus gene replication and transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Calpain inhibitors inhibit the replication of echovirus 1, possibly by targeting the activities of calpain 1 and 2 (Upla et al, 2008). Pyrrolidine dithiocarbamate (PDTC) inhibits polyprotein processing of entero-and cardioviruses by transporting zinc ions into the cells with different mechanisms depending on the virus species (Krenn et al, 2005;Lanke et al, 2007). For PDTC, a mechanism via the ubiquitin-proteasome pathway is also proposed for the inhibitory effect on coxsackievirus B3 (CVB3) infection (Si et al, 2005).…”
Section: Introductionmentioning
confidence: 99%